KUALITAS PELAYANAN SISTEM INFORMASI MANAJEMEN NIKAH (SIMKAH) PADA MASA PANDEMI COVID-19 (STUDI DESKRIPTIF DI KUA KECAMATAN JUNREJO KOTA BATU) - Abdul Rahman Haq al Alif; Khoirul Asfiyak; Shofiatul Jannah (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
In Circular Number: P-006/DJ.III/Hk.00.7/06/2020 Regarding Services Towards a Covid-Safe Productive Society. Wedding services during this pandemic require the bride and groom to register their marriage online via the simkah website. Based on initial observations, it was found that many people did not understand the procedures and mechanisms for online marriage registration due to the lack of socialization regarding this new policy and there is also an error on the simkah website. The formulation of the problem from this research is How is the Quality of Marriage Management Information System (SIMKAH) Services during the Covid-19 pandemic. This type of research is a case study with a descriptive approach, Data collection is done through passive observation, then by semi-structured interviews,and the documentation. Quality of Service of the Marriage Management Information System (SIMKAH) during the Covid-19 pandemic at the KUA, Junrejo District, the availability of facilities and infrastructure (Tangibles / Physical evidence) Having competent human resources (Reliability / Reliability) Serving fairly and putting the interests of the applicant first (Emphaty / Reliability) Concern) Receive criticism and facilities (Responsiveness / Responsiveness), carry out socialization to the community (Emphaty / Concern), do not charge service fees (Assurance / Guarantee)